A Study to Assess the Effectiveness of Protective Techniques of Facial Pressure Ulcer Among Patients on Non-invasive Mechanical Ventilation in PCCM Department at Pt. B.D. Sharma PGIMS Rohtak - Sahil Nandal; Hemwati; Pawan Kumar Singh (International Journal of Emergency and Trauma Nursing and Practices, 2025)
The study aimed to assess the effectiveness of protective techniques in preventing facial pressure ulcers among patients on non-invasive mechanical ventilation in the Post-Critical Care Management (PCCM) department at Pt. B.D. Sharma PGIMS, Rohtak. Facial pressure ulcers are a common complication in patients undergoing non-invasive mechanical ventilation, often resulting from prolonged pressure on facial tissues due to mask contact. This descriptive study involved a sample of 60 patients receiving non-invasive mechanical ventilation. Protective techniques such as repositioning the patient, the use of cushioning materials, and frequent skin assessments were implemented as interventions. Data were collected through observational checklists, which included factors like mask fit, frequency of repositioning, and incidence of facial pressure ulcers. The results demonstrated a significant reduction in the occurrence of facial pressure ulcers among patients who received these protective measures compared to those who did not. This study highlights the importance of preventive strategies in the PCCM department and emphasizes the role of nursing staff in implementing such techniques to enhance patient care. The findings suggest that systematic use of protective techniques can significantly reduce the risk of facial pressure ulcers, improving patient comfort and reducing treatment costs. Further research is recommended to explore the long-term effects of these protective interventions and their application in other critical care settings.
Keywords: PCCM department; Protective techniques; facial pressure ulcers; non-invasive mechanical ventilation; patient care